Analisis Kapabilitas Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Bintan Dalam Pengelolaan Inovasi Sistem Pelayanan Administrasi Kependudukan Dan Catatan Sipil (Sipanducapil) Dengan Perspektif Dynamic Governance - Rahmat Rahmat; Shahril Budiman; Suhardi Mukhlis (Jurnal Ilmu Pemerintahan, 2026)
This study is entitled "Analysis of the Capability of the Department of Population and Civil Registration of Bintan Regency in Managing the Innovation of the Population Administration and Civil Registry Service System with a Dynamic Governance Perspective." Driven by national bureaucratic reform and digital government expansion, the local government launched the Civil Registry and Administration Service System Innovation, or Si Pandu Capil, to provide population administration services online. This study aims to analyze the institutional capabilities of the Bintan Regency Population and Civil Registry Department in managing the Si Pandu Capil innovation through a dynamic governance perspective. The researcher utilizes the theoretical framework proposed by Neo and Chen (2007), evaluating three core organizational dimensions: routines, resources, and resilience. This study employs an exploratory research design with a qualitative approach. Located at the Population and Civil Registration Office of Bintan Regency, the research informants include employees and local residents using Si Pandu Capil, selected via purposive sampling. Data collection methods involve direct observation, structured interviews, and comprehensive documentation. The results demonstrate that the Department of Population and Civil Registration possesses the capability to manage the Si Pandu Capil innovation, although it is not yet optimal. Consequently, this study recommends that the government update the existing Standard Operating Procedures (SOP) and Public Service Standards for this digital platform. Additionally, the department should officially establish the Innovation Implementation Team, accelerate new feature developments, and enhance coordination with the Office of Communication and Information.